I2‐Promoted Direct C−H Sulfenylation of Isoquinolin‐1(2H)‐ones with Sulfonyl Chlorides. Issue 1 (16th December 2020) - Yang, Cai‐Yun; Li, Xia; Liu, Bo; Huang, Guo‐Li
Abstract: A simple, efficient, and green method for the iodine‐promoted regioselective C‐4 sulfenylation of isoquinolin‐1(2 H )‐ones using commercially available aryl sulfonyl chlorides as the sulfur source was described under metal‐ and solvent‐free conditions. The reaction proceeded smoothly under simple conditions to obtain 4‐arylthioisoquinolin‐1(2 H )‐ones in moderate to good yields, and showed high regioselectivity, broad substrate scope, and good functional group tolerance. A radical reaction mechanism involving ArS . radicals as key intermediates is proposed for the present transformation. Abstract : Iodine‐promoted regioselective C‐4 sulfenylation of isoquinolin‐1(2 H )‐ones using commercially available aryl sulfonyl chlorides as the sulfur source under metal‐ and solvent‐free conditions was described. These methods provide an alternative and facile synthetic route to access a series of 4‐arylthio‐substituted isoquinolin‐1(2 H )‐one derivatives in moderate to good yields. This is a useful, time‐efficient, and scalable procedure for the construction of C(sp 2 )−S bonds.